ANALYSIS MULTIRESOLUTION - Nuñez Ramirez, Luis Miguel (2010)
Before the concept has been formalized Analysis Multiresolution AMR, base construction orthonormal wavelet should be too difficult. For Therefore, the study of AM R becomes important and therefore construction of Wavelets is viable. In the construction of a wavelet Ψ, we determine a scale function Φ, then build your Analysis Associated multiresolution; soon passed has built Ψ with desired properties for applications.